Algebraic Thinking Profiles of Junior High Schools’ Pupil in Mathematics Problem Solving - Anis Wahyu Rahmawati; Dwi Juniati; Agung Lukito (International Journal of Trends in Mathematics Education Research, 2019)
Algebra is one of concept that must be learned  by pupils. It is because the algebraic concept can be used in all areas of mathematics. One of the ways that is used to develop pupils' algebraic abilities is to think algebraically. While one of the ways  to develop pupils' algebraic thinking skills is to adapt pupils with mathematical problem solving. The purpose of this study is describing algebraic thinking profiles of junior high school pupils in mathematical problem solving. The description of pupils' algebraic thinking profiles is explained based on six indicators namely generalization, abstraction, analytic thinking, dynamic thinking, modeling and organization. This research is a qualitative study using test and interview methods. The research subjects consisted of one student in each student with high mathematical abilities, medium mathematical abilities and low mathematical abilities. The results showed that there were differences in algebraic thinking  of junior high school pupils  in solving mathematics in terms of mathematical abilities. Based on research data shows  that pupils with high mathematical abilities always think algebraically in each problems solving are given, while students with medium and low ability do not always think algebraically in each of problem solving.